Watertight papers to float on - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Water Management, Proceedings of a CTA Seminar, Cordoba, Spain, 20-25 September 1999 CTA, 2001. 224 pp. ISBN 92 9081 2400 CTA number 1048, 20 credit points